Central obesity as measured by waist circumference is predictive of severity of lower urinary tract symptoms - Lee, Richard K.; Chung, Doreen; Chughtai, Bilal; Te, Alexis E.; Kaplan, Steven A. (BJU international, 2012)
Study Type – Prognosis (cohort) Level of Evidence 2a What's known on the subject? and What does the study add? The metabolic syndrome, or Syndrome X, has traditionally been associated with an increased risk of cardiovascular disease and sexual dysfunction. Emerging data however now suggest that the metabolic syndrome may also have a heretofore unrecognized negative effect on voiding function as well. Weight loss through either behavioural modification or bariatric surgery has been shown to lead to improvement in stress and urge incontinence as well as LUTS. A potential relationship may be drawn between obesity and BPH. This study adds the knowledge that WC can represent a simple metric not only for elements of the metabolic syndrome but also for worsened voiding. These obese men may be at high risk of male pelvic dysfunction. OBJECTIVES • To determine if central obesity as measured by waist circumference (WC) is a risk factor in metabolic dysfunction, which includes hypertension, dyslipidaemia and type 2 diabetes (DM2). • To test the hypothesis that central obesity and WC are associated with and predictive of the severity of voiding dysfunction. METHODS • Men aged ≥40 years with moderate or severe lower urinary tract symptoms (LUTS, International Prostate Symptom Score ≥ 8) with no previous treatment were included for study. • Subjects were divided into three groups according to WC (<90, 90–99 and ≥100 cm). • Baseline parameters including International Prostate Symptom Score, prostate volume, serum prostate‐specific antigen, presence of erectile dysfunction and ejaculatory dysfunction, and the prevalence of hypertension, coronary artery disease and DM2 were compared among the three WC categories. • The association between WC and all parameters assessed was tested using multivariate logistic regression analysis. RESULTS • In the 409 consecutive men analysed, WC was significantly and positively associated with prostate volume, serum prostate‐specific antigen and International Prostate Symptom Score. • Higher WCs were also significantly associated with a greater prevalence of hypertension, coronary artery disease, DM2 and obesity as well as the presence of erectile dysfunction and ejaculatory dysfunction. CONCLUSIONS • Increased WC is associated with worsened voiding. • There was a significantly increased prevalence of components of the metabolic syndrome in patients with higher WC. • Obese men, in particular those with other features of the metabolic syndrome, are at increased risk of male pelvic dysfunction and can be easily recognized by measurement of WC.